Introducing English Literature as a Medium for Promoting Local Cultural Tourism through Digital Content: Pengabdian - Yasin, Mohammad Ilham; Fikri, Moh. Hilman; Putra, Rizky Perdana Bayu; Wahyuni, Sri; Dwi, Maharani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service project endeavours to present English literature as a new vehicle for advancing local cultural tourism through online media. As the world remains culturally influenced by globalization, there is an increasing necessity to equip local communities, particularly youth, with creative means of conserving and disseminating heritage in a compelling manner. With English literary expression and internet media brought together, students are invited to compose poems, short stories, and stories that promote local knowledge and tourist attractions. Field activity like practice of the story based on actual cultural experience and classes on English literature and content creation online are part of the program. The end products are electronic literary pieces that can be posted on the world wide web, and they are meant to market local culture to the global community. The project not only improves people's English and computer skills but also instills pride in local heritage and community identity.